THE ANALYSIS OF TRAVEL CHARACTERISTICS AND THE SCHOOL BUS PROVISION PLAN BASED ON STUDENTS’ TRANSPORTATION MODE - Rozandi, A.; Agustien, M.; Arliansyah, J. (Science and Transport Progress, 2019)
Purpose. This study was conducted to obtain the characteristics of respondents and travel modes that are still dominated among private vehicle users. Methodology. This analysis was done using Microsoft excel and SPSS Ver. 25 for Windows. Findings. The results showed that the factors affecting the use of transportation modes for students journeys at one time to and from school are as follows: a) sex (X1), b) age (X2), c) monthly pocket money (X3), d) distance (X6), e) long trips departure (X7 ), f) leave travel expenses (X8), g) the frequency of the return trip (X10), h) the distance of the return trip (X11), i) the long way home (X12) and j) the cost for going home (X13). The opportunity of providing school bus may get good responses because the students would prefer to choose a mass transportation integrated with the school and giving good service, safety, less cost and its affectivity. In fact, it is not only in pedestrian offenders who have close travel distance and short-time travel of leaving for school and back home. Originality. There have been many studies discussing public transportation. However, this study limits only in discussing the use of school bus regarding students’ transport modes. Practical value. Generally, this study contributes positive outputs in some aspects, such as: economics, management and safety. Indeed, the existence of school bus will help students who have some difficulties, including distance, economical problem and so on.